EVALUATION OF EDUCATION IMPLEMENTATION OF TRAINING PIM III IN AGENCY OF HUMAN RESOURCE DEVELOPMENT - Kencana Sari; Mukneri Mukhtar; Yetti Supriyati (IJHCM (International Journal of Human Capital Management), 2017)
This study is a qualitative research aims to find out how the implementation of leadership level III training at Human Resources Development Board of Province of South Sumatera based on: (1) participant's satisfaction covers: participant's satisfaction to widyaiswara or resource person, participant's satisfaction to organizer committee service, participant's satisfaction on training materials, participant's satisfaction on training schedule, Participants on training facilities and infrastructure, and participant's satisfaction with the training consumption; (2) learning activities include: participant activity in learning process, widyaiswara activity or resource in learning process, and organizer activity of organizer in learning process; (3) changes in the behavior of alumni after returning to their respective duties, including: behavioral changes in implementing management functions, behavior change in task delegation, behavior change in coordination, and behavior change in decision making; (4) Impact of change in employment behavior of alumni to improve agency performance; and (5) Impact of change in work behavior of alumni to improve service quality of institution. Keywords: Evaluation, Educational, Training and Leaderships.